Epidemiological profile of mortality of patients victims of stroke in the state of Piauí from 2010 to 2020 (Research, Society and Development, 2023)
Objective: To determine the epidemiological profile of deaths due to stroke, which occurred in the state of Piauí, in the period between 2010 and 2020, registered in the ICD-10 category of DATASUS. Methods: This is a qualitative and quantitative, cross-sectional and descriptive study of epidemiological data on the mortality of patients suffering from stroke in the state of Piauí.  Data were obtained through the SUS Information System (DATASUS). Results: It was verified that there were 11.052 deaths from stroke in Piauí between January 2010 and December 2020. In addition, it was possible to observe that the most affected age group was 80 years old with 5387 cases, followed by the population from 70 to 79 years with 2891 deaths. With regard to color and race, brown people were the most affected with 7023. The average mortality rate in these years was 1004,72, the year with the highest mortality rate was 2013 and the lowest was 2016.  The most affected place of deaths were hospitals, with a total of 5,531 cases, followed by death at home with 5.294.Conclusion: It is possible to infer that the stroke has a high mortality rate in Piauí and that it is necessary to intervene in incident cases with the necessary treatments and rehabilitation therapies, as well as to promote actions to prevent controllable risk factors to minimize the effects of uncontrollable risk factors.